Exploring key success factors of sustainable start-up business - Mahyuni, Luh Putu; Rinaldi, Vincent (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
This research aims at exploring key success factors of local start-ups in transforming social and environmental problems into opportunities to develop sustainable start-up business. To address the research objective, case study was conducted on two local start-ups that have successfully attracted the attention of large investors, namely Bukaloka and Gringgo. In-depth interviews were conducted with two start-up’s leaders/founders, four start-up’s consumers, and three co-working space managers. Several documents were also collected directly from the informants to support and validate the results of the interviews. Codes and themes were identified from the interview transcripts analysis, some significant quotes were then taken to support the analysis. The results show that there are five factors explaining local start-ups’ ability to transform social and environmental problems into business opportunities, namely: first, strong internal motivation of the founders to address social and environmental problems; second, founders’ experience; third, sound understanding of market responses; fourth, effective design thinking; and finally, effective product co-creation strategy. The five factors are interrelated, with the founder’s motivation factor being the foundation of the start-ups’ building block.